ANALISIS KEPUASAN PENGGUNA SISTEM INFORMASI EVALUASI PENGAWASAN REALISASI ANGGARAN (SIEPRA) MENGGUNAKAN METODE End User Computing Satisfaction (EUCS) - Vivi Sahfitri (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2023)
This study aims to determine and analyze the extent to which the development of the Budget Realization Information System (SIEPRA) by evaluating in terms of the level of acceptance with the aim that SIEPRA can increase user satisfaction, simplify the process, ease and speed in obtaining services so that performance achievement reports and overview of the performance realization of the Regional Equipment Work Unit (SKPD) can be timely and correct. The research instrument used is a questionnaire. This research uses the End User Computing Satisfaction (EUCS) method which will be used to determine SIEPRA user satisfaction. The variables to be measured are Content, accuracy, format, ease of use and timeliness. This study aims to analyze the extent to which the development of SIEPRA by evaluating the level of acceptance with the aim that SIEPRA can increase user satisfaction using the EUCS method. Based on the results of the study, it can be seen that the level of satisfaction of SIEPRA users on each EUCS variable is 74.6% for the content variable, 76.6% for the Accuracy variable, 78.8% for the Format variable, 70.2% for the Ease of Use variable and 70.2% for the Timeliness variable. In general, the level of satisfaction of SIEPRA users based on the results of the study is in the category of satisfied and very satisfied with a percentage ³ 70%.